2012
DOI: 10.3382/ps.2012-02213
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression in pectoral skeletal muscle of chickens as influenced by dietary methionine

Abstract: Effects of dietary methionine (Met) on pectoralis muscle development and the effect that Met as a nutritional substrate has on protein expression of skeletal muscle cells of pectoralis muscle of chickens were evaluated in this study. Broiler chickens received a common pretest diet up to 21 d of age and were subsequently fed either a low (LM) or high Met (HM) diet (0.41 vs. 0.51% of diet) from 21 to 42 d of age. Dietary deficiency was shown in vivo judging by the depression in breast meat weight and yield when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 33 publications
5
25
1
1
Order By: Relevance
“…Previous research [1] indicated that an increase in dietary methionine (Met) from 0.41% (8% higher than the 0.38% as recommended by NRC [2]) to 0.51% (34% higher than the NRC…”
Section: Description Of Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research [1] indicated that an increase in dietary methionine (Met) from 0.41% (8% higher than the 0.38% as recommended by NRC [2]) to 0.51% (34% higher than the NRC…”
Section: Description Of Problemmentioning
confidence: 99%
“…Therefore, dietary Met supplementation induces lower relative myofibrillar protein solubility, which may improve breast meat tenderness. In addition, Zhai et al (2012) [1] reported that Met supplementation may lead to greater nutrient absorption into muscle cells. This may affect breast meat nutrient composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methionine-induced alterations of metabolic pathways controlling lipogenesis may also be involved (Takahashi and Akiba, 1995). Zhai et al (2012) muscle protein deposition might have been due to sarcoplasmic rather than myofi brillar hypertrophy. Because of the diminishing returns pattern observed in all the response criteria studied, exponential model by Littell et al (1997) was used to estimate the bioavailability of MHA-FA relative to DLM.…”
Section: Resultsmentioning
confidence: 99%
“…VII show that, in comparison with equimolar levels of DLM, the MHA-FA availability was lower in all cases, the greatest diff erence being found in carcass and breast meat yields. The sensitivity of both absolute and relative breast meat yield to dietary methionine levels has been demonstrated in many studies (Schutte and Pack, 1995;Zhai et al, 2012). Also, it has been shown that the optimal levels of SAA (as well as lysine) for breast meat deposition are higher than for body weight gain (Bartov and Plavnik, 1998).…”
Section: Treatmentmentioning
confidence: 97%